Alkaloid biosynthesis in medicinal crop kratom (Mitragyna speciosa) varies with postharvest, genetic, and seasonal factors - Zhang, Mengzi; Lyndon, Annabella; Kanumuri, Siva Rama Raju; Sharma, Abhisheak; Pearson, Brian J.; McCurdy, Christopher R.; Chen, Jianjun (Frontiers in Plant Science, 2025)
IntroductionKratom (Mitragyna speciosa), a medicinally valuable ethnobotanical tree native to Southeast Asia, has traditionally been used to combat fatigue and enhance productivity. Recently, it has gained attention in North America and Europe for its potential therapeutic applications, particularly in pain management and opioid withdrawal, positioning it as a candidate for drug development. Postharvest processing is a critical stage that influences chemical transformations of bioactive compounds, yet its impact on kratom remains poorly understood.MethodsThis study investigated the effects of withering duration, drying temperature, cultivar, and season on kratom alkaloid composition and concentration. In Study I, leaves of cultivar Hawaii underwent four withering durations (0, 12, 24, 72 h) followed by drying at five temperatures (−40, 25, 40, 60, 80 °C). In Study II, leaves of cultivar MR-Malaysian were tested under two withering durations (0, 12 h) and two drying temperatures (25, 60 °C). Both studies were conducted across two seasons.ResultsWithering generally increased mitragynine concentrations by 14-65% (w/w) in 'Hawaii' and 3-8% in 'MR-Malaysian' in leaf alkaloid extracts. A 12-h withering followed by drying below 40 °C enhanced speciogynine and paynantheine in 'Hawaii' by 37-48% and 35-67%, respectively. Low drying temperatures preserved mitragynine, speciogynine, and paynantheine across cultivars. The average 7-hydroxymitragynine content in leaf alkaloid extracts ranged from 0.02-0.04% and was detected only in specific seasons, varying by cultivar, suggesting genotype-environment interactions.DiscussionThis study demonstrates for the first time that kratom alkaloid composition and concentration are substantially influenced by genotype, season, and postharvest handling. These findings underscore the importance of optimizing postharvest processing strategies to enhance beneficial alkaloid profiles in kratom.